(untitled) (LIS TODAY, 2021)
COVID-19 has been spreading and killing hundreds of thousands of people worldwide thereby necessitating measures are required that will drastically reduce the spread of the pandemic. The preliminary investigation of the researchers concretized the reality that Corona virus is yet to have a cure or endorsed vaccine from the World Health Organization (WHO) – a bird’s eye view possibility in measuring the pandemic response success. The option left therefore, is to take precaution in curtailing the further spread through behavioral measures – namely; keeping a safe distance, avoiding social gatherings, washing hands, and reducing social contact and also, treating the noticed symptoms speedily. Although these measures are universal, advanced countries have evolved better approaches in prevention and control of the spread through the use of artificial intelligence (AI), big data, cloud computing, block chain and 5G, which have effectively improved the efficiency of the countries’ efforts in epidemic monitoring, virus tracking, prevention, control and treatment, and resource allocation. This research therefore draws the methods used in those advanced countries in contrast to those of developing or developed countries in fighting against the pandemic while considering recorded successes that will serve as a guide for pandemic response and preparedness plans.